Ayah Teladan Sebagai Peletak Dasar Iman Anak - Sostenis Nggebu; Yusnoveri Chung (Manna Rafflesia, 2022)
The problem of this research is that there is a phenomenon that children need an exemplary father in fostering their faith, so that they experience a personal encounter with God in Jesus Christ, believe in Him, and obey His word. This article uses literature study. The results reveal that the child's introduction to God is the responsibility of the father as the head of the family as well as the spiritual leader for all members of the family. Fathers nurture children spiritually so that they have a close relationship with God, experience new life in Jesus Christ and be able to overcome temptations and still rely on Jesus Christ in the midst of the restlessness of the world. Active involvement in spiritual development will have a positive impact on children's lives so that children enjoy their growth and development in a healthy and meaningful way. Children can also record a father figure leadership model for the child's self-development. And in the future the child will be able to carry on this impact in his life, in particular becoming a potential model father for his son.